2005
DOI: 10.1111/j.1471-0528.2005.00788.x
|View full text |Cite
|
Sign up to set email alerts
|

General obstetrics: A randomised controlled trial of metronidazole for the prevention of preterm birth in women positive for cervicovaginal fetal fibronectin: the PREMET Study

Abstract: Objective To determine whether metronidazole reduces early preterm labour in asymptomatic women with positive vaginal fetal fibronectin (fFN) in the second trimester of pregnancy.Design Randomised placebo-controlled trial.Setting Fourteen UK hospitals (three teaching).Population Pregnacies with at least one previous risk factor, including mid-trimester loss or preterm delivery, uterine abnormality, cervical surgery or cerclage.Methods Nine hundred pregnancies were screened for fFN at 24 and 27 weeks of gestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(75 citation statements)
references
References 33 publications
2
72
1
Order By: Relevance
“…Despite this, 17% of respondents do not routinely prescribe antibiotics for women symptomatic for preterm birth. Of those who do prescribe antibiotics for PPROM, erythromycin is the most commonly prescribed antibiotic and this is reflective of best practice recommendations [28][29][30][31]. The findings from this survey reflect the conflicting evidence on the routine use of cervical cerclage for preventing preterm birth [32][33][34], with 13% of consultant obstetricians routinely inserting an elective cervical cerclage in women with a history of one or more mid-trimester miscarriages (15-22 weeks gestation), whilst 70% would consider inserting an emergency cervical cerclage.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, 17% of respondents do not routinely prescribe antibiotics for women symptomatic for preterm birth. Of those who do prescribe antibiotics for PPROM, erythromycin is the most commonly prescribed antibiotic and this is reflective of best practice recommendations [28][29][30][31]. The findings from this survey reflect the conflicting evidence on the routine use of cervical cerclage for preventing preterm birth [32][33][34], with 13% of consultant obstetricians routinely inserting an elective cervical cerclage in women with a history of one or more mid-trimester miscarriages (15-22 weeks gestation), whilst 70% would consider inserting an emergency cervical cerclage.…”
Section: Discussionmentioning
confidence: 99%
“…Metronidazole alone was used in six studies. 8,9,11,16,19,23 Only one individual study showed a significant advantage to metronidazole use in reducing PTB prior to 37 weeks gestation. 23 Two individual studies showed no significant effect; 9,16 whereas the remaining three all showed a significant adverse effect on preterm delivery with metronidazole use.…”
Section: Clindamycin Metronidazole and Erythromycin Alone Or In Comentioning
confidence: 93%
“…10,18 For the three studies that principally assessed risk based on previous preterm delivery (with or without abnormal vaginal flora), one used metronidazole, 23 one used clindamycin 22 and one used a combination of metronidazole and erythromycin. 24 For the two studies assessing risk based on positive fetal fibronectin, one used metronidazole, 8 and the other a combination of metronidazole and erythromycin. 21 The studies in this review followed a randomised double-blind, placebo-controlled standard.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a randomized controlled trial of 7 days of metronidazole for the prevention of preterm birth in women positive for cervicovaginal fetal fibronectin (the PREMET Study) showed that in this selected non-IBD population, preterm delivery (<37 weeks) was increased by metronidazole therapy (33/53 vs. 18/46 for placebo, CI 1.05–2.4) [30]. Loebstein et al [31] prospectively enrolled and followed up 200 women exposed to fluoroquinolones (norfloxacin, ciprofloxacin, ofloxacin) during gestation.…”
Section: Resultsmentioning
confidence: 99%